2020
DOI: 10.1002/jcad.12301
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Client Attrition in a University‐Based Community Counseling Clinic

Abstract: The purpose of this study was to investigate how symptom distress, social role, interpersonal relationships, gender, age, number of supports, and education level predict client attrition in a community sample. Using binary logistic regression and cross‐sectional data, the authors examined the predictive impact of 8 variables on adult client attrition in a university‐based community counseling clinic. Results indicated that education level, interpersonal relationships, and number of supports significantly predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…First, the rate of PT is known to vary widely across treatment settings with estimates ranging anywhere from 0 to 74.2% (Swift & Greenberg, 2012 ). Also, data specific to PT in counselor training clinics are rarely published in professional journals and, when such data are available, researchers tend to operationalize PT using different classification criteria including therapist‐determination or the missed last session method (Harris et al., 2020 ; Lampropoulos et al., 2009 ). To ensure comparability across studies, it is critical for researchers to thoroughly describe how PT was measured.…”
Section: Discussionmentioning
confidence: 99%
“…First, the rate of PT is known to vary widely across treatment settings with estimates ranging anywhere from 0 to 74.2% (Swift & Greenberg, 2012 ). Also, data specific to PT in counselor training clinics are rarely published in professional journals and, when such data are available, researchers tend to operationalize PT using different classification criteria including therapist‐determination or the missed last session method (Harris et al., 2020 ; Lampropoulos et al., 2009 ). To ensure comparability across studies, it is critical for researchers to thoroughly describe how PT was measured.…”
Section: Discussionmentioning
confidence: 99%
“…Research on racial identity as a predictor of retention in therapy has mixed findings. Some studies have not found the race to be a predictor of retention in psychotherapy (Harris et al, 2020;Swift & Greenberg, 2012) or couple therapy (Fischer et al, 2018), whereas others have found that racially minoritized participants are less likely to be retained in individual psychotherapy baseline (6 months only). These findings are discussed with relevance to clinicians and researchers to recruit and retain more diverse and marginalized participants in couple interventions and follow-up research.…”
Section: Racial Statusmentioning
confidence: 99%
“…Research on racial identity as a predictor of retention in therapy has mixed findings. Some studies have not found the race to be a predictor of retention in psychotherapy (Harris et al, 2020; Swift & Greenberg, 2012) or couple therapy (Fischer et al, 2018), whereas others have found that racially minoritized participants are less likely to be retained in individual psychotherapy (Cooper & Conklin, 2015) and treatment programs (Fortuna et al, 2010; McClendon et al, 2020). Williams et al (2005) found that Black American clients were less likely to be retained than European American clients, but only when clients were female and made less than $10,000 per year.…”
Section: Introductionmentioning
confidence: 99%
“…In a qualitative study of client experiences of counselor multicultural competence, Pope-Davis et al (2002) found that the ways in which clients perceived power in the counseling relationship played a role in how much they disclosed to their counselor and how they recovered from the counselor cultural errors in the sessions. More recently, Harris et al (2020) investigated the predictors of attrition in a university-based community counseling clinic. Education level, interpersonal relationships, and number of supports significantly predicted attrition, while gender, age, symptom distress, social role, and race did not (Harris, 2020).…”
Section: Client Experiences In Training Clinicsmentioning
confidence: 99%